2016
DOI: 10.1111/jai.13244
|View full text |Cite
|
Sign up to set email alerts
|

Life history and status of Shortnose Sturgeon (Acipenser brevirostrumLeSueur, 1818)

Abstract: Summary Shortnose Sturgeon = SNS (Acipenser brevirostrum) is a small diadromous species with most populations living in large Atlantic coast rivers and estuaries of North America from New Brunswick, Canada, to GA, USA. There are no naturally land‐locked populations, so all populations require access to fresh water and salt water to complete a natural life cycle. The species is amphidromous with use of fresh water and salt water (the estuary) varied across the species range, a pattern that may reflect whether f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 116 publications
0
18
0
Order By: Relevance
“…Larvae have 4-5 days to find food before starvation, and this critical period is one of the primary drivers of sturgeon population growth rate (Gross, Repka, Robertson, Secor, & Van Winkle, 2002). Studies on other sturgeon species, such as shortnose sturgeon (Acipenser brevirostrum) and white sturgeon (Acipenser transmontanous), have found that larvae consume primarily drifting prey (Buckley & Kynard, 1981;Kynard, Parker, Kynard, & Horgan, 2014;Kynard et al, 2016), while juveniles shift to benthic prey (Radtke, 1966). Optimal growth of early life stage green sturgeon has been found to occur between temperatures of 15-19°C (Mayfield & Cech, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Larvae have 4-5 days to find food before starvation, and this critical period is one of the primary drivers of sturgeon population growth rate (Gross, Repka, Robertson, Secor, & Van Winkle, 2002). Studies on other sturgeon species, such as shortnose sturgeon (Acipenser brevirostrum) and white sturgeon (Acipenser transmontanous), have found that larvae consume primarily drifting prey (Buckley & Kynard, 1981;Kynard, Parker, Kynard, & Horgan, 2014;Kynard et al, 2016), while juveniles shift to benthic prey (Radtke, 1966). Optimal growth of early life stage green sturgeon has been found to occur between temperatures of 15-19°C (Mayfield & Cech, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Based on ontogenetic diet shifts in white sturgeon and shortnose sturgeon (Buckley & Kynard, 1981;Kynard et al, 2014Kynard et al, , 2016Radtke, 1966), we hypothesise that as larval green sturgeons increase in total length, they shift from zooplankton to benthic macroinvertebrates (BMI). Based on ontogenetic diet shifts in white sturgeon and shortnose sturgeon (Buckley & Kynard, 1981;Kynard et al, 2014Kynard et al, , 2016Radtke, 1966), we hypothesise that as larval green sturgeons increase in total length, they shift from zooplankton to benthic macroinvertebrates (BMI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spawning behavior in most sturgeon species is difficult to observe, because spawning occurs in deep and sometimes turbid rivers . Polyandrous spawning, represented by several males following a single female and competing for an optimum spawning position, was reported in a number of species such as Atlantic sturgeon (A. o. oxyrinchus; Hilton, Kynard, Balazik, Horodysky, & Dillman, 2016), Gulf sturgeon , shortnose sturgeon (A. brevirostrum; Kynard et al, 2016), and white sturgeon . However, males also tend to remain near the spawning grounds, and spawn several times with different females .…”
Section: Mating Typementioning
confidence: 99%
“…There is abundant evidence of spawning site fidelity in various sturgeon species (Bruch, Haxton, Koenigs, Welsh, & Kerr, 2016;DeHaan, Libants, Elliott, & Scribner, 2006;Forsythe et al, 2012;Kynard et al, 2016;Pollock et al, 2015;Sulak et al, 2016;Welsh, Hill, Quinlan, Robinson, & May, 2008). In addition, differentiated genetic structure observed in some populations with no visible fragmentation is considered to be another indication of strong spawning site fidelity (Bruch et al, 2016;Hildebrand et al, 2016;Pollock et al, 2015;Sulak et al, 2016).…”
Section: Homing Behaviormentioning
confidence: 99%